Entrepreneurship Research Journal (De Gruyter, 2011)
Positioned as the premier research journal within the field of entrepreneurship, the Entrepreneurship Research Journal (ERJ) is a forum for scholarly discussion on entrepreneurs and their activities, contexts, processes, strategies and outcomes. It seeks to encourage a scholarly exchange between researchers from any field of study who focus on entrepreneurs and includes both theoretical and empirical articles.